A study of the effective prevention of illegal open dumping at residential area in Malaysia / Nur Fahimah Jalaludin - Jalaludin, Nur Fahimah (2014)
This report explained about the effectiveness prevention of illegal open dumping at residential area in Malaysia. Nowadays, the rapid development of Malaysia contributed to increase in the amount of waste. The waste management in Malaysia displays a variety of problems, including low collection coverage on average due to some factors such as the inaccessibility by vehicles of some areas, irregular collection services, lacking equipment used for waste collection, crude open dumping and burning without air and water pollution control, insufficient legal provisions and resources constraints. These problems are caused by various factors which have an impact on the development of effective waste management systems in Malaysia (Lau, 2004). Besides that, this report also identify some guidelines for prevention of illegal open dumping. The effective illegal dumping prevention program also involves government, industry and community working together to identify the problem in a defined area. There are several ways can be approached to prevent the illegal open dumping which are cleanup efforts, community program and ordinance for targeted enforcement. The Local Authority and public play main role in waste management. The local government should realize their role to assure there are effective waste programs to improve the environment in Malaysia. Meanwhile, the public also should realize the awareness to the environment. By this roles, the illegal dumping problem can be overcome.